Nonclinical Safety of the Sodium-Glucose Cotransporter 2 Inhibitor Empagliflozin. (November 2014) - Bogdanffy, Matthew S.; Stachlewitz, Robert F.; van Tongeren, Susan; Knight, Brian; Sharp, Dale E.; Ku, Warren; Hart, Susan Emeigh; Blanchard, Kerry
Empagliflozin, a selective inhibitor of the renal tubular sodium-glucose cotransporter 2, was developed for treatment of type 2 diabetes mellitus. Nonclinical safety of empagliflozin was studied in a battery of tests to support global market authorization. Safety pharmacology studies indicated no effect of empagliflozin on measures of respiratory or central nervous system function in rats or cardiovascular safety in telemeterized dogs. In CD-1 mouse, Wistar Han rat, or beagle dogs up to 13, 26, or 52 weeks of treatment, respectively, empagliflozin exhibited a toxicity profile consistent with secondary supratherapeutic pharmacology related to glucose loss and included decreased body weight and body fat, increased food consumption, diarrhea, dehydration, decreased serum glucose and increases in other serum parameters reflective of increased protein catabolism, gluconeogenesis, and electrolyte imbalances, and urinary changes such as polyuria and glucosuria. Microscopic changes were consistently observed in kidney and included tubular nephropathy and interstitial nephritis (dog), renal mineralization (rat) and tubular epithelial cell karyomegaly, single cell necrosis, cystic hyperplasia, and hypertrophy (mouse). Empagliflozin was not genotoxic. Empagliflozin was not carcinogenic in female mice or female rats. Renal adenoma and carcinoma were induced in male mice only at exposures 45 times the maximum clinical dose. These tumors were associated with a spectrum of nonneoplastic changes suggestive of a nongenotoxic, cytotoxic, and cellular proliferation-driven mechanism. In male rats, testicular interstitial cell tumors and hemangiomas of the mesenteric lymph node were observed; both tumors are common in rats and are unlikely to be relevant to humans. These studies demonstrate the nonclinical safety of empagliflozin.